Mesh objective continuum damage models for ductile fracture. (1st December 2015) - Larsson, Ragnar; Razanica, Senad; Josefson, B. Lennart
Summary: During machining processes, the work piece material is subjected to high deformation rates, increased temperature, large plastic deformations, damage evolution and fracture. In this context the Johnson‐Cook failure model is often used even though it exhibits pathological mesh size dependence. To remove the mesh size sensitivity, a set of mesh objective damage models is proposed based on a local continuum damage formulation combined with the concept of a scalar damage phase field. The first model represents a mesh objective augmentation of the well‐established element removal model, whereas the second one degrades the continuum stress in a smooth fashion. Plane strain plate and hat specimens are used in the finite element simulations, with the restriction to the temperature and rate independent cases. To investigate the influence of mesh distortion, a structured and an unstructured meshes were used for the respective specimen. For structured meshes, the results clearly show that the pathological mesh size sensitivity is removed for both models. When considering unstructured meshes, the mesh size sensitivity is more complex as revealed by the considered hat‐specimen shear test. Nevertheless, the present work indicates that the proposed models can predict realistic ductile failure behaviors in a mesh objective fashion. Copyright © 2015 John Wiley & Sons, Ltd.